Exploring the Relationship between Religious Faith and Persistence Through Intertextuality - brendaly e drayton (Adult Education Research Conference, 2016)
This paper draws upon intertextuality to explore how an African American male adult learner uses his religious faith as a resource for persisting in an adult literacy program. The findings indicate that religious faith was not simply a coping mechanism but a resource for redefining learner identity.
Keywords: African-American men; Intertextuality; Learner Identity; Persistence; Spirituality